Prevalence of obesity in male in relation to dietary intake and physical activity level - Abbas, Muhammad; Khan, Alam; Khattak, Muhammad Muzaffar Ali Khan (Asian Network for Scientific Information, 2003)
The present study was conducted to assess the prevalence of obesity in relation to diet and physical activity levels (PALs) in Tehsil Mardan, of the North West Frontier Province (NWFP), Pakistan. Three cities, three towns and three villages were selected from the whole Tehsil. Hundred households in each city, town and village were randomly selected. A male individual of above 30 years age from each selected household was interviewed. In this way a total of 900 male subjects were surveyed. The information collected include their height, weight, food intake for three alternate days, occupation and other activities. Prevalence of obesity was determined by Body Mass Index (BMI). The average values showed 7 and 34% prevalence of obesity (BMI = > 30) and overweight (BMI = 25-30), respectively in Tehsil Mardan. Prevalence of obesity and overweight was more in cities than towns and more in towns than villages. The average energy intake was 2522?449 kcal/day. The relative contribution of protein, fat and carbohydrate to the total energy intake was 12, 33 and 56%, respectively. The energy intake was positively correlated with BMI (r = 0.799) and their PALs were negatively correlated with BMI (r = - 0.398). The present study alarms that obesity is becoming a major health problem of concern in Tehsil Mardan. Therefore, early nutritional interventions are required.